Assembly initiated production as a prerequisite for mass customization and effective manufacturing - Anišić, Zoran (Strojniški vestnik, 2008)
The paper deals with a review of a complex IPS-DFA methodology with a purpose of rating and improving design characteristics regarding the aspect of the assembly process. The approach has to be applied at the level of the product assortment, basic product structure and at the component level, aiming to achieve two primary goals' rationalization of the part count and the optimization of handling and fitting parts, through the developed tools for assembly suitability enhancement. Comprehensiveness of the methodology, especially at the product assortment level, simultaneously enables increasing suitability for mass customization. The paper provides an insight into the results of circular pumps product family application with a special emphasis on the consequences concerning mass customization.
Keywords: proizvodnja; montaža; načrtovanje; rotacijske črpalke